FIRST RUSSIAN EXPERIENCE OF USING THE INTEGRATED SYSTEM OF LASER THERMOABLATION THERAPY IN THE TREATMENT OF METASTATIC LIVER CANCER - D. V. Sidorov; S. O. Stepanov; M. V. Lozhkin; L. O. Petrov; O. V. Gutz; A. A. Kostin; A. G. Isaeva (Исследования и практика в медицине)
Extensive liver resections are the main method of treatment of patients with primary and metastatic liver cancer, which allows the noticeable prolongation of life. In patients with a reduced functional reserve of the liver or a missing volume of the remaining liver parenchyma, these interventions become impossible because of the increased risk of postresectional acute hepatic insufficiency. One of the most modern and promising ways to overcome this obstacle is the use of minimally invasive methods of tumor destruction. This article presents two observations of the clinical application of the laser ablator “Echolaser X4”: open laser ablation of the metastatic focus with subsequent atypical liver resection and percutaneous laser ablation of the metastasis of the neuroendocrine tumor into the liver. The presented experience testifies to the justification of using laser destruction of metastatic malignant liver tumors and demonstrates the possibilities of laser thermoablation therapy in patients who can not perform radical surgical treatment.